The Ebro river basin - Barcelo, Damia; Petrovic, Mira; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
The Ebro is a typical Mediterranean river characterized by seasonal low flows and extreme flush effects, with important agricultural and industrial activity that has caused heavy contamination problems. This volume deals with soil-sediment-groundwater related issues in the Ebro river basin and summarizes the results generated within the European Union-funded project AquaTerra. The following topics are highlighted: Hydrology and sediment transport and their alterations due to climate change, aquatic and riparian biodiversity in the Ebro watershed, occurrence and distribution of a wide range of priority and emerging contaminants, effects of chemical pollution on biota and integration of climate change scenarios with several aspects of the Ebroâ??s hydrology and potential impacts of climate change on pollution. The primary objective of the book is to lay the foundation for a better understanding of the behavior of environmental pollutants and their fluxes with respect to climate and land use changes
The physical framework and historic human influences in the Ebro River; Hydology and sediment transport; Hydrological impacts of climate change on the Ebro River basin; Dams and Reservoirs in the lower Ebro River and its effects on the river thermal cycle; Dissolved fluxes of the Ebro River basin (Spain): Impact of main lithologies and role of tributaries; Aquatic and riparian biodiversity in the Ebro watershed: prospects and threats; Persistent organic pollutants in water, sediments and biota in the Ebro River basin; Origin, occurrence and behaviour of brominated flame retardants in the Ebro basin; Pesticides at the Ebro River delta: Occurrence and toxicity in water and biota; Sources, occurrence and environmental risk assessment of pharmaceuticals in the Ebro River basin; Mercuty in aquatic organisms of the Ebro River basin; Drugs of abuse along the Ebro River basin: occurrence in surface and wastewater and derived consumption estimations; Biological effects of chemical pollution in feral fish and shellfish populations from Ebro River. From molecular to individual level responses, Climate change, water resources and pollution in the Ebro Basin a towards an integrated approach; Chemometric analysis and mapping of environmental pollution sources in the Ebro River basin; Experiences and lessonsÂ learned on the implementation of the water framework directive in selected European river basins.
Electronic reproduction.
Keywords: Environmental sciences -- Spain -- Ebro River Valley; Environmental chemistry -- Spain -- Ebro River Valley; Hydraulic engineering -- Spain -- Ebro River Valley; Pollution -- Spain -- Ebro River Valley; Analytical biochemistry; Geochemistry; Marine sciences -- Spain -- Ebro River Valley